An enhancement in the petrophysical evaluation in a vuggy carbonate gas reservoir by integrating the core data and empirical methods, Zagros basin, south of Iran - Safavi, Seyed Javad; Maldar, Ramin (Journal of Asian Earth Sciences: X, 2024)
•Thin section, image log and rock physics data were applied to pinpoint the vugs.•The VDL approach were utilized to reveal vuggy-bearing intervals.•In presence of vug, it is necessary to use the variable porosity exponent (m) instead of a constant “m” value.•Petrophysical evaluation were enhanced using the Lucia-derived “m”, in vug zones. The presence of vuggy pore types poses challenges in accurately assessing effective porosity. This study focuses on the significant scientific issue of improving petrophysical evaluation in vuggy carbonate gas reservoirs. The Kangan Formation is one of the main gas reservoir formations in the southern Zagros region, Iran. The main objective of the current research is to distinguish and exclude the influence of vuggy pore types from effective porosity in the reservoir pay zones of the Kangan reservoir. In the current research, a combination of full suite logs, image logs, core analysis, and thin section studies was employed. The image logs illustrate that vuggy porosity is abundant in the Kangan Formation and these results are confirmed by the available core thin sections, specifically in Zone Kangan_B; Additionally, the cross plots of compressional velocity versus bulk density and total porosity, as a part of rock physics study, indicate the characteristics of the vuggy reservoir. Two methods are utilized to quantify vuggy porosity. The first method, the Velocity Deviation Log (VDL) approach, identifies various available pore types, especially vugs. The second method is a newly proposed approach that can exclude vuggy porosity from the computed effective porosity. In this novel approach, a variable porosity exponent (m) is derived by adopting the Lucia equation to exclude vuggy porosity from the effective porosity computations. Thus, petrophysical evaluation can be implemented based on the constant and variable “m”. Comparing both petrophysical results, it is evident that the amounts of effective porosity and water saturation are modified in the vuggy-bearing intervals. Applying the proposed approach will improve the accuracy of petrophysical properties and lead to the proper calculation of the hydrocarbon volume in the carbonate reservoir rocks containing isolated vugs, particularly in gas-bearing reservoirs where conventional logs are affected by gas contents.